Beyond English-Only: Master’s Students’ Perceptions of Translanguaging Challenges and Strategies in Indonesian EFL Higher Education - Nanda Efriani; Failasofah Failasofah; Reli Handayani; Hadiyanto Hadiyanto; Mukhlash Abrar (Journal of Educational Sciences, 2026)
In Indonesian EFL higher education, the use of students’ first language alongside English remains a debated issue, as multilingual practices are often perceived as a barrier to English development. However, translanguaging provides a perspective that views learners’ entire linguistic repertoire as a resource for meaning-making and academic learning. This study aimed to explore the challenges experienced by Indonesian EFL master's students when using translanguaging in classroom interaction and the strategies they employed to utilize translanguaging as a learning resource. Employing a qualitative case study design, data were collected through semi-structured interviews with five Indonesian EFL master's students and analyzed using thematic analysis. The findings revealed that students experienced challenges related to academic language complexity, uncertainty in managing language choice, and psychological factors. Nevertheless, students strategically employed translanguaging in reading academic literature, classroom discussions, academic writing, and presentations. Translanguaging functioned as a cognitive and interactional scaffold that supported comprehension, knowledge construction, participation, and English academic development. The study concludes that translanguaging should not be viewed as a replacement for English but as a purposeful multilingual resource that facilitates learning in Indonesian EFL higher education contexts.